Sentiment Analysis of Telkom University using the Long Short-Term Memory and Word2Vec Feature Expansion - Alfarel, Ahmad; Hasmawati, Hasmawati; Bunyamin, Bunyamin (Universitas Negeri Padang, 2024)
One of Indonesia's top private universities is Telkom University, and branding is an important aspect of maintaining its reputation. In the digital era, social media has become the main platform for people to express their opinions on various topics, including educational institutions. This research aims to analyze public sentiment towards Telkom University on platform X (formerly Twitter) by using the Long Short-Term Memory (LSTM) method and Word2Vec Feature expansion. The data used consists of 6,627 tweets collected between November 2022 and November 2023. Sentiments were categorized into